Peer effects, Financial Decisions and Industry Concentration: A review - Isma Zaighum; Dr. Mohd Zaini Abd Karim (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- This article reviews literature related to peer effects and different financial decisions. It further summarizes the theory and motives that drive peer effects. Also, the study highlights the influence of industry concentration on peer interaction in financial decision making. This content analysis of scantily available peer effect literature has been performed to highlight the significance of peer effects in financial decision making like investment, cash holding, leverage and many more. Most of the existing peer effects literature focuses on the U.S. However, peer effects also occur in other countries but empirical evidence is comparatively limited. But, managers may take into consideration their industry peers especially if their firms are operating in highly competitive environments. Design/Methodology- Content analysis approach is applied to review prevailing financial literature on peer interactions and financial decisions with a special focus on industry concentration in explaining the peer effects. Practical Implications- As the prime focus of managerial decisions is to maximize the firm’s value. Hence, information about peers would be helpful in making better decisions, especially in highly competitive environments. Also, this review of selected literature provides pathways for future research in investigating the motives of peer effects.